Fraudulent Financial Statement: Evidence from Statement on Auditing Standard No. 99 - Suyanto Suyanto (Gadjah Mada International Journal of Business, 2009)
The goals of this study are to empirically identify fraud risk factors and construct a model to predict the likelihood of financial statement frauds based on SAS No. 99. Employing logistic regression on 143 firms, this research  finds that fraud risk factor proxies for Pressure—net profit/total assets—and Opportunity— inventory/total assets ratio, related party transactions, and Big 4—are significantly associated with fraudulent financial statements, whereas none of the fraud risk factor proxies for Rationalization is significantly associated with fraudulent financial statements. Consistent with prior research, it seems that the likelihood of fraudulent financial statements is easier to be observed publicly using fraud risk factor proxies for Pressure and Opportunity rather than Rationalization. The constructed model can correctly classify firms with a relatively high success rate.